2010
DOI: 10.1002/acr.20225
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of acupuncture for osteoarthritis of the knee: Effects of patient‐provider communication

Abstract: Objectives There is conflicting evidence on the efficacy of Traditional Chinese Acupuncture (TCA), and the role of placebo effects elicited by acupuncturists’ behavior has not been elucidated. We conducted a 3-month randomized clinical trial in patients with knee osteoarthritis to compare the efficacy of TCA to sham acupuncture, and examine the effects of acupuncturists’ communication style. Methods Acupuncturists were trained to interact in one of two communication styles: ‘high’ or ‘neutral’ expectations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
179
3
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(190 citation statements)
references
References 33 publications
5
179
3
3
Order By: Relevance
“…Finally, all findings were drawn in a correlational, rather than a causal, direction. Studies adopting experimental methods are needed to establish causal relationships, for example, employing randomized control design [35] to study effects of multimorbidity on cue expression, or manipulating the type of emotional cue provision [36] to study clinician responses.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…Finally, all findings were drawn in a correlational, rather than a causal, direction. Studies adopting experimental methods are needed to establish causal relationships, for example, employing randomized control design [35] to study effects of multimorbidity on cue expression, or manipulating the type of emotional cue provision [36] to study clinician responses.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…105 The second trial, of knee osteoarthritis, randomised participants to an acupuncturist who provided either a high expectation of success or neutral expectation, or to a waiting list, with those allocated to initial treatment further randomised to sham or verum acupuncture. 107 Again, these trialists found that participants randomised to receive treatment from an acupuncturist with higher expectations did better on two out of the three primary outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized controlled trial of acupuncture for OA, traditional Chinese acupuncture was found not to be superior to sham acupuncture. However, "acupuncturists' styles had significant effects on pain reduction and satisfaction, suggesting that the analgesic benefits of acupuncture can be partially mediated through placebo effects related to the acupuncturist's behavior" [29] . Telephone contact is shown to be a useful intervention that can enhance the functional status of OA patients by reducing pain and improving psychological health [30] .…”
Section: Placebo Response In Oamentioning
confidence: 99%